2003
DOI: 10.1046/j.1525-1314.2003.00463.x
|View full text |Cite
|
Sign up to set email alerts
|

SHRIMP U–Pb dating of coesite‐bearing zircon from the ultrahigh‐pressure metamorphic rocks, Sulu terrane, east China

Abstract: This paper provides further evidence for the ongoing discussion as to whether the Dabie UHPM belt formed in Triassic or Palaeozoic time, and whether the Sulu UHPM belt formed in Triassic or Neoproterozoic time. Combined use of laser Raman spectrometer (LR), cathodoluminescence imaging (CL), and ion probe U-Pb in-situ dating (SHRIMP) provided accurate ages of UHPM from rocks collected from Weihai, NE Sulu UHPM belt. LR was used to identify coesite and other UHP minerals as inclusions in zircon separates from an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(81 citation statements)
references
References 22 publications
6
73
1
1
Order By: Relevance
“…SHRIMP U-Pb dating on coesite-bearing domains of metamorphic zircon [67][68][69][70][71][72][73] has bracketed the UHP metamorphic event between 242±2 Ma and 227±2 Ma ( Figure 5). This not only provides resolution to the contrasting views, but also rules out the possibility that the Dabie UHP metamorphism occurred in the Early Paleozoic as suggested by garnet Ar-Ar dating [61,62] .…”
Section: Age Of the Uhp Metamorphismmentioning
confidence: 99%
“…SHRIMP U-Pb dating on coesite-bearing domains of metamorphic zircon [67][68][69][70][71][72][73] has bracketed the UHP metamorphic event between 242±2 Ma and 227±2 Ma ( Figure 5). This not only provides resolution to the contrasting views, but also rules out the possibility that the Dabie UHP metamorphism occurred in the Early Paleozoic as suggested by garnet Ar-Ar dating [61,62] .…”
Section: Age Of the Uhp Metamorphismmentioning
confidence: 99%
“…4a) when the ultramafic-mafic or mafic magmas intruded the pre-existing crust in Neoproterozoic. Yang et al (2003) reported an SHRIMP discordia upper-intercept age of 1 821 Ma from a Rongcheng eclogite. This zircon may record a component of the pre-existing continental crust.…”
Section: Neoproterozoic (~850 Ma) Juvenile Mafic Magmatismmentioning
confidence: 99%
“…Previous studies of zircon U-Pb dating have been mostly devoted to the G-type eclogite (e.g., Ames et al, 1996;Rowley et al, 1997;Hacker et al, 1998Hacker et al, , 2000Ayers et al, 2002;Liu et al, 2004aLiu et al, ,b, 2005Zheng et al, 2004Zheng et al, , 2005a, with a few to the P-type eclogite (Ayers et al, 2002;Rumble et al, 2002;Yang et al, 2003;Zhang et al, 2005). Thus this study examines the M-type eclogite in the Dabie orogen ( Fig.…”
Section: Geological Settings and Samplesmentioning
confidence: 99%
“…The results show two groups of Triassic age: (1) 243 ± 1 Ma for jadeite quartzite (Liu and Jian, 2004), 244 ± 5 Ma for granitic gneiss (Wan et al, 2005), and 245 ± 14 Ma for granitic gneiss ; (2) 228 ± 2 Ma for the jadeite quartzite (Liu and Jian, 2004), 234 ± 4 Ma (Liu and Xu, 2004), 231 ± 4 Ma (Liu et al, 2004a), 227 ± 2 Ma (Liu et al, 2004b), and 226 ± 2 Ma (Wan et al, 2005) for granitic gneiss, and 227 ± 5 Ma for amphibolized peridotite (Yang et al, 2003). It appears that there are the two episodes of zircon growth in the field of coesite stability during the Triassic UHP metamorphism.…”
Section: Timing Of Metamorphic Zircon Growthmentioning
confidence: 99%